Edukasi Dan Pemeriksaan Kesehatan Melalui Kebidanan Komunitas dan Fome III di Kelurahan Koto Luar Kecamatan Pauh Kota Padang - Laila Rahmi; Aldina Ayunda Insani; Fitrayeni; Nur Avivah; Rezki Amellia Putri; Ainun Mardiah Lubis; Anisa Ulfah; Suhaila Damayanti Br Nasution; Tiara Wulandari; Ranny Shabrina; Humairah Faradila (Warta Pengabdian Andalas, 2024)
Community midwifery and Family Oriented Midwifery Education (FOME) is a form of application of technological knowledge in the field of midwifery in the Midwifery Professional Midwifery Study Program, which is comprehensive throughout a woman's life cycle. One of the targets in the community is women of reproductive age, with the problem of the low number of family planning (KB) acceptors among couples of childbearing age (PUS). Community midwifery and FOME activities aim to discover the health conditions and problems in a community, especially in midwifery, so that solutions to these problems can be carried out. This activity uses a descriptive observational method with questionnaires and interviews in the RT 03 and RT 04 RW 02 community, Koto Luar Village, Pauh District, Padang City, West Sumatra. The activity results were 71 heads of families (KK) in RT 03/02 and 42 families in RT 04/02. As many as 96% of PUS in RT 03/02 and 56% in RT 04/02 were not family planning acceptors. Another problem was that 87% in RT 03/02 and 90% in RT 04/02 did not receive health education in the last 6 months, and as many as 56% in RT 03/02 and 78% in RT 04/02 did not carry out routine weighing of toddlers every the month. As a result of advocacy with community stakeholders and the Pauh Community Health Center, it was decided to provide education and health checks related to the problems encountered. The education and health checks that have been carried out provide information that benefits the community by increasing self-empowerment and dealing with existing problems.